(untitled) (REMUNOM, 2026)
The main objective of this work is to investigate the level of cooperation, decentralization, and dialogue that exists between municipalities due to the federal pact. The federal pact was established by the 1988 Federal Constitution with a peculiarity: the so-called triune federalism, which recognizes the existence of three federative entities: the Union, the states, and the municipalities. Municipalities possess their own political, administrative, and financial competencies, but this decentralization also entails serious problems. Municipalities are autonomous, but many of them do not produce enough to sustain and develop themselves, and often municipal, state, and federal responsibilities are confused with the implementation of the National Education System. By the end of 2025, this scenario had changed, with the creation of a clear document outlining what each entity should do. This was linked to the new Fund for the Maintenance and Development of Basic Education and the Enhancement of Education Professionals, officially made permanent in 2020, and the mass participation in Education Development Arrangements and municipal public consortia, which led to a significant improvement in the Basic Education Development Index of several municipalities. From a methodological point of view, a Bibliographic and Documentary Review was used, this being a quantitative-qualitative research, of a basic nature and of a theoretical genre. The main results show that cooperation between municipalities is indispensable for public policies to take place and achieve their objectives based on the federative pact, since, as demonstrated, many municipalities have improved in development, especially regarding economies of scale applied to education.